2014
DOI: 10.11113/mjfas.v6n1.171
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly imprinted polymers for solid phase extraction of orghanophosphorus pesticides

Abstract: Molecularly imprinted polymer-solid phase extraction (MIP-SPE) adsorbent was prepared for the analysis of selected organophosphorus pesticides(OPPs) in environmental sample. In this work, the influence of process parameters on the preparation of imprinted polymer is presented. In theprocedure of polymerization, molecularly imprinted bulk polymer was prepared using quinalphos and methacrylic acid (MAA) as template molecule and functional monomer, respectively. The influence of the following parameters on recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The increased pore volume provides more space for the template molecules to reside, promoting the higher binding capacity and potentially enhancing the selectivity of the MIP. The presence of a template molecule in the MIP synthesis allows the production of MIP with a larger surface area, average pore radius, and total pore volume as compared to the NIP, thus leading to improved recognition performance for the template molecule [51,52] . Hence, the higher surface area, average pore radius, and total pore volume of the MIP (2VP) than that of NIP (2VP) showed that MIP (2VP) had a more favorable structure for ATZ recognition and binding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased pore volume provides more space for the template molecules to reside, promoting the higher binding capacity and potentially enhancing the selectivity of the MIP. The presence of a template molecule in the MIP synthesis allows the production of MIP with a larger surface area, average pore radius, and total pore volume as compared to the NIP, thus leading to improved recognition performance for the template molecule [51,52] . Hence, the higher surface area, average pore radius, and total pore volume of the MIP (2VP) than that of NIP (2VP) showed that MIP (2VP) had a more favorable structure for ATZ recognition and binding.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a template molecule in the MIP synthesis allows the production of MIP with a larger surface area, average pore radius, and total pore volume as compared to the NIP, thus leading to improved recognition performance for the template molecule. [51,52] Hence, the higher surface area, average pore radius, and total pore volume of the MIP (2VP) than that of NIP (2VP) showed that MIP (2VP) had a more favorable structure for ATZ recognition and binding. These properties are essential for achieving high specificity and affinity of MIP (2VP) towards ATZ template molecule, making the MIP (2VP) an efficient and selective material for ATZ detection and removal applications.…”
Section: Brunauer-emmett-teller (Bet) Analysismentioning
confidence: 99%
“…Based on the results (Table-2), the synthesized MIP had larger specific surface area, average pore radius and pore volume as compared to NIP. This was due to the presence of template molecule that contributed for the imprinting effect in MIP [17]. The solvent used in the polymerization process played important role in the pore formation within the macroporous polymers.…”
Section: Brunauer-emmett-teller Analysis Of Synthesized Polymers Of Mmentioning
confidence: 99%
“…These showed high enrichment factors and efficiencies(185). Keeping these points into consideration, Kosteret al(186) used MIPs as coating materials for the formation of silica coated fibers used in SPME.Moreover, Sanagi et al(187) synthesized MIPs and used as adsorbents in solid phase extraction (SPE) method. Various reports are available for micro-extraction of analytes using MIPs-SPME coated fibers and coating techniques for the preparation of micro-extraction probes (above, the applications of nanoparticles have good recognition around the world for the micro-extraction of analytes present in complex samples or at trace level in aqueous conditions.…”
mentioning
confidence: 97%